QUO VADIS UNDANG-UNDANG POKOK AGRARIA? Suatu Tinjauan Terhadap Permasalahan Pertanahan di Usia Undang-undang Pokok Agraria yang ke Lima Puluh Delapan Tahun - Benny Djaja (Faculty of Law - Tarumanagara University, 2018)
Disputes in the world of business are not something to write home about. Amongst all the business-related sectors, one that often rears disputes is the agrarian sector. This is due to the close relationship between development and the need for land, as one of the primary needs of humankind. Therefore, a review and comprehensive exposition of disputes within the land sector and aspects of peaceful mediation of said disputes are needed to gain a deeper understanding of ways to achieve more effective and efficient land dispute resolution. In order to achieve these goals and objectives, an in-depth analysis is needed on the extent to which Undang-undang Pokok Agraria (The Agrarian Law) accommodates the resolution of the agrarian disputes and problems, as well as, in relation to the existence of implementing regulations of Undang-undang Pokok Agraria that support the resolution of land disputes that arose or which may arise in the future. Currently disputes over land can be resolved through the means of a lawsuit in the Private Court of Law or through peaceful mediation. Peaceful mediation of land disputes can be carried out both within and outside the Court of Law. Based on the research, mediation in the court has a low rate of success mainly because of the “out for war” mentality of the parties involved which have been formed prior to entering the mediation process. With the settlement of cases through the Judiciary Court of Law becoming a go-to option in the majority of land dispute resolution, the high costs and length of time commonly incurred in such process greatly hampers the resolution of numerous land disputes and tends to be a field of